Precision medicine using different biological DMARDs based on characteristic phenotypes of peripheral T helper cells in psoriatic arthritis. (2nd April 2018) - Miyagawa, Ippei; Nakayamada, Shingo; Nakano, Kazuhisa; Kubo, Satoshi; Iwata, Shigeru; Miyazaki, Yusuke; Yoshikawa, Maiko; Yoshinari, Hiroko; Tanaka, Yoshiya
Abstract: Objectives: We sought to investigate the selection of specific biological DMARDs (bDMARDs) based on characteristic lymphocyte phenotypes for treating PsA. Methods: Of 64 patients with PsA resistant to MTX, 26 underwent bDMARDs therapy selected according to phenotypic differences in peripheral helper T cells on 8-colour flow cytometry. The efficacies of this strategic treatment and the standard treatment administered to the other 38 patients were evaluated at 6 months. Results: The 26 patients with PsA in the strategic treatment group were classified into the following four types based on peripheral blood analysis: (i) CXCR3 + CCR6 − CD38 + HLA-DR + activated Th1 cell–predominant type, (ii) CXCR3 − CCR6 + CD38 + HLA-DR + activated Th17 cell–predominant type, (iii) Th1/Th17-high type and (iv) Th1/Th17-low type. Accordingly, ustekinumab was administered to the activated Th1 cell–predominant patients, secukinumab to the activated Th17 cell–predominant patients, secukinumab or TNF inhibitor to the Th1/Th17-high patients, and TNF inhibitor to the Th1/Th17-low patients. After 6 months of strategic treatment, there was a significant decrease in simplified disease activity index (SDAI) (from 16.2 to 3.52), DAS28 (ESR) (from 4.13 to 2.27) and psoriasis area and severity index (from 8.36 to 2.40). Low disease activity by SDAI was achieved in 24 (92.3%) of the 26 patients. The rate of low disease activity achievement according to SDAI at 6 months was significantly higher in the strategic bDMARDs treatment group compared with that of the standard bDMARDs treatment group. Conclusion: Strategic treatment in which different bDMARDs were selected according to phenotypic differences in helper T cells showed significantly higher efficacy than standard bDMARD therapy, indicating the value of precision medicine.